Accuracy of position of cutting and drilling guide for sagittal split guided surgery: a proof of concept study. Issue 8 (October 2020) - Philippe, B.
Graphical abstract: Abstract: The benefits of three-dimensional planning and guided surgery have been realised over the last few years in maxillofacial surgery. Reproducing the exact positioning of the cutting and drilling guides on the flat mandibular angles defined by the engineer is a challenge for the surgeon and for the reliability of guided bilateral sagittal split osteotomy. Reference screws positioned on the skeleton before the acquisition of medical computed tomographic data can provide a fixed landmark that can be used during surgery and by the engineer during the design phase. The objective of this proof of concept in vitro study is to calculate the accuracy obtained for guides positioned by inserting a reference screw. The precision obtained for 30 guides following the insertion of 30 reference screws on 15 mandibular models was analysed. The models were scanned using an optical scanner and compared to CAD-CAM projects. The mean (SD) absolute position (in)-inaccuracy is 0.1616 (0.1141) mm for the entire guide surface and 0.13143 (0.0835) mm for the rim surface. The results indicate that the use of reference screws is efficient, and so they can be used to position guides accurately during guided bilateral sagittal split osteotomy.